Annual Update in Intensive Care and Emergency Medicine 2013 - Vincent, Jean-Louis.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The Yearbook compiles the most recent developments in experimental andclinical research and practice in one comprehensive reference book. Thechapters are written by well recognized experts in the field of intensive care and emergency medicine. It is addressed to everyone involved in internal medicine, anesthesia, surgery, pediatrics, intensive care and emergency medicine.
Emergencies -- Infections -- Antimicrobials -- Sepsis therapies -- Adjunct therapies -- Hemodynamic optimization -- The peripheral circulation -- Cardiac arrest -- Monitoring -- Transthoracic monitoring -- Lung cells -- Intravenous fluids -- Perioperative problems -- Mechanical ventilation -- Renal failure -- Renal replacement therapies -- Neurological issues -- Physiotherapy and ICU weakness -- Organization and outcomes.
Keywords: Medicine; Emergency medicine; Critical care medicine; Internal medicine; Medicine & Public Health; Medicine/Public Health, general; Intensive / Critical Care Medicine; Emergency Medicine; Internal Medicine